TA‘ADDUD AL-JUMU‘AH PADA MASYARAKAT MLAJAH MENURUT MADHHAB SYAFI‘IYAH - Imamul Arifin (Jurnal Sosial Humaniora, 2017)
The jumu'ah prayer is the two raka'at performed at the time of the Zuhurprayer every Friday. Every Moslem is not considered to be denied theobligation of performing his jumu'ah prayers by performing the Zuhurpraying if there are no things that allow him to leave the jumu'ah prayers.Along with the development of the era, the mosques were very developed evenwe can find easily in various regions. However, it turns out that not allmosques can be said that the mosque is eligible to serve as a place of jumuahprayer. One of them in Mlajah-Bangkalan area, there are some people whoconsider the amount of pilgrims jumuah must be in accordance withacceptable criteria. Seeing this phenomenon, at least the term baldah must befully discussed thoroughly to facilitate in reviewing this problem.